Analysis of the Morphology, Rheology, and Clinical Applicability of a Hybrid Injectable with Hyaluronic Acid and Hydroxyapatite - Santos, Pâmela Leticia; Magdalena, Aroldo Geraldo [UNESP]; Ficho, Ana Carolina [UNESP]; da Silveira Pessanha, Stephanie; Rosa, Jorge Luiz; de Lima Romeiro, Rogério; Queiroz, Thallita Pereira (Springer Nature, 2024)
Background: Treating signs of aging requires skeletal restructuring, facial contour redefinition, and sagging skin treatment. Hence, HarmonyCa® was recently introduced in the market, combining hyaluronic acid and hydroxyapatite. However, there are no studies evaluating the physicochemical properties of this material. Purpose: To analyze the morphology, rheology, and clinical applicability of HarmonyCa® over a 180-day follow-up. Methods: A morphological analysis with scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) and rheology measurement with a rheometer. The clinical applicability analysis included a tissue ptosis patient who received the product and was reassessed 30 and 180 days after applying HarmonyCa®. Results: SEM and EDS analyses showed two distinct morphologies related to hydroxyapatite and hyaluronic acid. The rheological measurements of HarmonyCa® showed G′ and G″ of 51.56 and 44.01 Pa, respectively. The tan δ value was 0.8503, and G* was 108.1 Pa. The clinical outcomes were satisfactory. Conclusion: HarmonyCa® presents a good synergy between hyaluronic acid and hydroxyapatite. Also, the rheological analysis showed moderate viscosity for the product, with a clinical indication for subcutaneous application. Level of Evidence IV: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.
Keywords: Calcium hydroxyapatite; Filler; Hyaluronic acid